Activity Based Management (ABM) Method to Improve the Efficiency of Education Financing at SMK Sore Ponorogo - Yuli Lapansari; Yusuf Susian; Roufi'ul Mustafidah (INTEGRATIA: Journal of Education, Human Development, and Community Engagement, 2024)
In carrying out the educational process in educational institutions, one of the important factors is financing management. Financing management functions as planning, implementation, control, and evaluation related to the financial process in educational institutions. Activity Based Management is an approach that focuses management attention on activities carried out to increase customer value and provide benefits derived from that value. Efficiency can be done properly if the policies taken are based on observations and realities in the field so that the program that set can run optimally. This study aims to describe and analyse Activity Based Management (ABM) based budgeting in improving the efficiency of education financing at SMK Sore Ponorogo. The research method used is descriptive qualitative which seeks to explain and describe the findings in the field and was associated with the theory found. The results of this study were (1) SMK Sore Ponorogo has implemented the Activity Based Management (ABM) method (2) Based on the application of the Activity Based Management (ABM) method, it was found that there were non-value-added activities that needed to be minimized (3) After applying ABM, cost efficiency can be found after reducing activities so that cost stability is found.